Pemanfaatan Daun Sereh dan Kulit Jeruk untuk Pencegahan Gigitan Nyamuk Aedes Aegypti - Mukaromah, Ana Hidayati; Saptaningtyas, Ragil; Wardoyo, Fandhi Adi; Maharani, Alifia Inggit; Nova, Dini Adelia; Shofwana, Fatya; Fitriana, Laily; Hikmah, Murti Amalia Nur; Wulandari, Nungky; Setianingsih, Sri; Prititasari, Rahma; Kurniawan, Sodikin (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
Dengue Hemorrhagic Fever is Dengue is a disease caused by mosquito vectors. Breaking the chain of transmission in larval vases can be prevented by spraying using natural ingredients as safe and environmentally friendly larvicides, including lemongrass leaves and orange peel. The aim of this activity is to use waste lemongrass leaves and orange peels to prevent Aedes aegypti mosquitoes, as well as being able to make mosquito coils. The community service program partner is the principal of SDN Dombo 1 Sayung Demak. This service method begins with a location survey of SDN Dombo 1 Sayung, making poster media, a lecture on Clean and Healthy Lifestyle, the benefits of lemongrass leaves and lemon peel, as well as presenting a practical video on making lemongrass leaf and lemon peel solution, packaging and labeling. Before implementation, a pre-test was carried out and after implementation, a post-test was carried out. Results: The average pre-test score was 75.36 and the students' post-test was 97.39 (an increase in knowledge of 29.23%). In conclusion, this community service activity increased students' knowledge. Lemongrass Leaf and Orange Peel Spray can be used to prevent Aedes aegypti mosquito bites.